The Synthesis of Myth and Reality in the Poetics of the Historical Novel: The Epic Tradition in the Works of Vasily Yan and Isajon Sultan - Djuraeva , Farahbonu (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
The epistemological architecture of historical narratives necessitates a continuous recalibration of the cognitive boundary between documentary fact and archetypal mythologem. This study deconstructs the structural and semantic mechanisms of myth-reality synthesis within the chronotopes of novels by V. Yan and I. Sulton. By analyzing a lexical corpus of 915,400 words, the frequency and functionality of archetypal markers were quantified. Extracted data indicate that in Yan’s prose, myth operates as a decorative element (folkloric background) complementing chronographic reality, whereas in Sulton’s works, myth functions as an ontological core that dictates historical events. The findings introduce novel metrics for comparative-typological analysis in literary studies.